Peculiarities of forming a root system of plum seedless in a fruit kennel with drip irrigation - N. N. Dubenok; A. V. Gemonov; A. V. Lebedev (Овощи России, 2020)
Relevance. Currently, there is a problem of satisfying the demand in the domestic market for fruit and berry products in accordance with current recommendations. One of the ways to intensify agricultural production is the use of resource-saving technologies, which include drip irrigation. The issues of regulating the water balance of the soil when growing planting material for fruit crops in modern conditions require experimental studies aimed at studying the biological characteristics of economically important plants and their reactions to the complex of external environmental factors.Methods. Field studies were conducted on the territory of the educational experimental farm of the Michurinsky Garden fruit growing laboratory of the Russian State Agrarian University - Moscow Timiryazev Agricultural Academy. A two-factor experience in the study of different ranges of moisture for the formation of varietal plum seedlings grafted on plum tree stock was laid in the spring of 2018. The first factor included options for maintaining soil moisture in the range of: 1) 60-80% of the lowest moisture capacity; 2) 70-90% of the lowest moisture capacity; 3) 80-100% of the lowest moisture capacity; 4) control (without irrigation). Plum varieties “Mashenka” and “Utro” were the second factor.Results. Constructed humidification contours according to the years of research and experimental options showed that drip irrigation contributes to the optimum moisture concentration in the soil for seedlings. The most developed root system compared with the control was obtained on irrigated options with maintaining humidity in the range of 70-90 and 80-100% of the lowest moisture capacity. Here, the maximum values of the volume of the root system, the number of roots and the average root length are obtained. It was revealed that in the variants with irrigation, the root system of seedlings spreads in the upper layer (mainly 20-30 cm) and stretches along the line with droppers.